PENTINGNYA KEPUTUSAN BIJAK: SEKOLAH INKLUSI ATAU LUAR BIASA - Nanin Gustia; Wahidah Fitriani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The aim of this research is to discuss how to choose the right school for children with special needs, including those with disabilities, and inclusion or special schools. Special schools offer a more focused approach to helping children with special needs, while inclusive schools promote inclusive and equitable education. To conduct this research, this research conducted an analysis of scientific literature related to this topic. The results of this analysis help us understand the debates and important issues related to educational placement decisions for children with special needs. The results of this research show that inclusive schools and special schools differ in terms of curriculum, teachers, facilities, methods and costs. The child's unique needs and available resources must be considered when making placement decisions. One of the main priorities is improving inclusive schools that support social inclusion and strengthening special schools that provide intensive support for children with special needs. This research increases our understanding of the importance of making informed decisions about the education of children with special needs; These decisions impact the development of children and society as a whole. This research reached the conclusion that it provides practical insight into educational decision-making processes and about efforts to create more inclusive and equitable educational environments for children with special needs.